2011
DOI: 10.1111/j.1399-3046.2011.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of alemtuzumab in the treatment of late acute renal allograft rejection

Abstract: Safety and efficacy of alemtuzumab in the treatment of AR in children after renal transplantation is unknown. Five episodes of refractory late AR in three children (three episodes in patient 1 and a single episode in patients 2 and 3 occurring after 7-23 months of transplantation) were treated with one dose of alemtuzumab as a rescue therapy. Four episodes (Banff IA-IB) in patients 1 and 2 reversed fully or partially with alemtuzumab, whereas patient 3 with Banff IB-IIA AR failed to respond. Patient 1 had recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Similar results were previously reported for kidney transplantation [2, 3]. Therefore, we hypothesized that NK cells have an important role in resisting microbial attack during alemtuzumab induction for several months while T-cells repopulate.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were previously reported for kidney transplantation [2, 3]. Therefore, we hypothesized that NK cells have an important role in resisting microbial attack during alemtuzumab induction for several months while T-cells repopulate.…”
Section: Introductionsupporting
confidence: 82%
“…CD52 is a glycoprotein expressed on approximately 95% of peripheral blood lymphocytes, natural killer (NK) cells, monocytes, macrophages, and thymocytes [1]. Lymphocyte depletion is expected to increase the risk of opportunistic infections [2, 3]. However, some studies have shown that the frequency of infectious diseases does not increase after organ transplantation [410].…”
Section: Introductionmentioning
confidence: 99%
“…Alemtuzumab is currently registered for the treatment of chronic lymphatic leukemia but data on the safety and efficacy of treatment of acute rejection after organ transplantation are scarce. Several studies reported the results in small groups of patients, merely demonstrating that recurrent or steroid-resistant rejection can be reversed with alemtuzumab (6)(7)(8)(9)(10). Randomized trials comparing alemtuzumab with other T cell-depleting agents for the treatment of acute rejection have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous issue of Pediatric Transplantation , Upadhyay et al. (1) describe three patients who are falling into the very unfortunate category described earlier. Specifically, they summarize their experience using alemtuzumab (Campath) as a last‐resort treatment option in late kidney transplant rejection in two teenagers, both with a reported history of non‐adherence and one younger child with a number of apparent oddities potentially contributing to the patient’s difficulties with rejections as well as infectious and other complications, for example, diarrhea, hypersplenism secondary to underlying autosomal recessive polycystic kidney disease, leukopenia and diarrhea in the first post‐transplant month leading to discontinuation of mycophenolate, and melatonin therapy.…”
mentioning
confidence: 95%